Si-based magnetic tunnel transistor with single CoFe base layer - Jang, SH; Kim, YW; Lee, JH; Kim, KY (AMER INST PHYSICS, 2005)
Magnetic tunnel transistors were prepared on Si(100) substrates by magnetron sputter deposition. By means of spin filtering through a single Co90Fe10 base layer, magnetocurrent ratios of 53%-55% and high transfer ratios of (1-2) x 10(-4) for emitter-base bias of 1.5-2 V were obtained at 77 K. The bias dependence of the collector current showed the square-law behavior. From the modified Bell-Kaiser model, attenuation lengths of majority and minority spins of hot electrons are expected as 40 +/- 5 and 16 +/- 1 A in the single Co90Fe10 layer, respectively. The decrease of transfer ratio was observed with decreasing base thickness from 80 to 30 A, which may be related to the extension of the (Co2Si and Fe) intermediate region formed at Co90Fe10/Si interface in the thinner base layer. (c) 2005 American Institute of Physics.
Keywords: HOT-ELECTRON TRANSPORT; METAL-SEMICONDUCTOR STRUCTURES; SPIN-VALVE TRANSISTOR; EMISSION MICROSCOPY; FILMS